Abuse of Psychotropic Drugs and Mental Health Challenges among the Youth of Port Harcourt, Rivers State - Ikuru Sampson(PhD) Ernest; Asor Confidence Asor (International Journal on Integrated Education, 2022)
The abuse of psychotropic drugs among youths in Nigeria is now a common phenomenon with a negative impact on society. In many psychiatric hospitals in Nigeria, a lot of young people are undergoing drug addiction treatment. This is becoming a social problem in Rivers State. It is against this backdrop that this study was undertaken to appraise the psychotropic drugs and their consequences on the mental health of youths in Port Harcourt, Rivers State. Structural questionnaires and oral interviews were used to collect data among parents, youths, and staff of NAFDAC and NDLEA. A total of 400 questionnaires were distributed, but 330 were recovered from the field. Simple statistical techniques, which comprised percentage, mean, and standard deviation, were used for the data analysis. The outcome of the study shows that the majority of youths depend on drugs to achieve greater efficiency, acquire long lasting energy, and alertness. The study further reveals the negative implications in terms of mental health risk are depression, schizophrenia, daytime sleepiness, and anxiety disorder, etc. This paper, therefore, concludes that the use of psychotropic drugs by youths is real and is assuming an alarming rate in the city of Port Harcourt. The study thus recommends, among other things, a collaborative effort between parents, government and non-governmental organisations (NGOs), as well as drug regulatory agencies such as the National Drugs Law Enforcement Agency (NDLEA), to train and re-orient children and youths on the negative effects of psychotropic drug abuse on their mental health, society, and human dignity